Paeonol Interferes With Quorum-Sensing in Pseudomonas aeruginosa and Modulates Inflammatory Responses In Vitro and In Vivo - Tang, Huaqiao; Yang, Dan; Zhu, Ling; Shi, Fei; Ye, Gang; Guo, Hongrui; Deng, Huidan; Zhao, Ling; Xu, Zhiwen; Li, Yinglun (Frontiers in Immunology, 2022)
Developing quorum-sensing (QS) based anti-infection drugs is one of the most powerful strategies to combat multidrug-resistant bacteria. Paeonol has been proven to attenuate the QS-controlled virulence factors of P. aeruginosa by down-regulating the transcription of QS signal molecules. This research aimed to assess the anti-virulence activity and mechanism of paeonol against P. aeruginosa infection in vitro and in vivo. In this study, paeonol was found to reduce the adhesion and invasion of P.aeruginosa to macrophages and resist the cytotoxicity induced by P.aeruginosa. Paeonol reduced the expression of virulence factors of P.aeruginosa by inhibiting quorum sensing, thereby reducing the LDH release and damages of P.aeruginosa-infected macrophages. Paeonol indirectly enhanced the ability of macrophages to phagocytose and kill P.aeruginosa by reducing bacterial virulence. In addition, paeonol exerts anti-inflammatory activity by reducing the synthesis of inflammatory cytokines and increasing the production of anti-inflammatory cytokines. Paeonol treatment significantly inhibited the TLR4/MyD88/NF-κB signaling pathway and inhibited the M1 polarization of P. aeruginosa-infected macrophages. Paeonol also significantly reduced the ability of P.aeruginosa to infect mice and reduced the inflammatory response in the lungs of infected mice. These data suggest that paeonol reduced the polarization of macrophages towards the M1 phenotype in vitro by inhibiting P. aeruginosa virulence factors. In addition, paeonol can also inhibit the release of inflammatory factors by macrophages by regulating the TLR4/MyD88/NF-κB pathway, but it does not affect the phagocytic ability of macrophages. This study supports the further development of new potential anti-infective drugs based on inhibition of QS and virulence factors.